Functional and Radiographic Outcomes of the Sauvé-Kapandji and Darrach Procedures in Rheumatoid Arthritis - Carl, Hannah M.; Lifchez, Scott D. (Journal of Hand and Microsurgery, 2019)
Background Deterioration of the distal radioulnar joint (DRUJ) in rheumatoid arthritis (RA) manifests as pain, weakness, and reduced range of motion. The Darrach and Sauvé-Kapandji (S-K) procedures are used when medical management fails to control these symptoms. However, there is a paucity of literature comparing the outcomes of these procedures. The purpose of this study is to compare the clinical and radiographic outcomes of the Darrach and S-K procedures in RA patients.Materials and Methods This is a retrospective, single institution cohort study of RA patients who underwent the Darrach or S-K procedure between 2008 and 2016. Ulnar translation, range of motion, and functional improvement were compared.Results Nine patients (13 wrists) underwent the Darrach procedure, and nine patients (11 wrists) underwent the S-K procedure. The average length of follow-up was 1.3 years. Pain, function, and range of motion improved in both groups. The degree of ulnar translation did not significantly change after either procedure.Conclusion Given their similar outcomes, we found no evidence that the S-K procedure is superior to the Darrach procedure or vice versa. However, when surgery is indicated for younger RA patients with DRUJ disease and ulnar translation, the S-K may be better suited to prevent radiocarpal joint dislocation.
Keywords: caput ulnae syndrome; Darrach procedure; rheumatoid arthritis; Sauvé-Kapandji procedure; ulna head